Electronically Excited States of Free Radicals - Igor V. Khudyakov (Physchem, 2023)
Formation of the excited doublet (D) and quartet (Q) states of free radicals under their photoexcitation is discussed. The relative positions of the D and Q states are compared to the positions of the photoexcited states of organic molecules (Jablonsky diagram). A number of representative cases of the excited states of free radicals detected by their transient absorption or emission are presented. A special case of the population having the lowest Q state in some radicals is discussed. A spin–statistical factor in the reactions of Q and D is debated.